Preliminary study on species composition and feeding guilds of birds found in Jengka Residential area and secondary forest of UiTM Jengka / Liliwirianis Nawi … [et al.] - Nawi, Liliwirianis; Mohaimey, Ahmad Syakil Ikmal; Md Isa, Nurun Nadhirah; Md. Jan, Sarah Laila; Shaikh Nasir, Nur Thabitah; Musa, Nor Lailatul Wahidah (Universiti Teknologi MARA Cawangan Pahang, 2021)
Bird species are now threatened by deforestation or forest clearance. This leads to the migration of many bird species in order to search for new places or habitat. This study aims to provide data on bird composition and bird diversity of two selected habitats; UiTM Jengka secondary forest and a residential area from Jengka namely Rantau Perintis. A total of 10 families, 15 species and 59 individuals are observed in both areas. The most dominant species in the secondary forest is Raphidura leucopygialis, while Apus pacificus has dominated the residential area. The values of Shannon’s Diversity index in the secondary forest is 2.207, which is higher than the residential area with the values of 1.629. However, the values of Simpson’s Diversity Index in residential area is 0.7733, which is lower than the secondary forest with the values of 0.8799. There are seven types of feeding guilds recorded in the study sites and insectivore are the most recorded species during this study.